Sintesis Bioplastik Berbahan Dasar Pati Jagung Dengan Penambahan Filler Selulosa Serat Daun Nanas (Ananas cosmosus) - Angga Dwina Putra; Idral Amri; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Conventional plastic waste is one of the most worrying issues for the environment because it can not be degraded by microorganisms. Bioplastic or biodegradable plastic is one of alternative solution to change conventional plastic, because bioplastics are easy to degrade. One of the potential materials to become the raw materials is corn starch and pineapple leaf fiber cellulose because it has high starch and hight cellulose. The general purpose of this research are to determine the impact and the best composition of the addition cellulose and glycerol in mechanical properties of bioplastic. The synthesis method is casting of corn starch, cellulose, and glycerol with composition of plasticizer is (0,5-1,5 gr) and composition of filler is (10–25 % b/b starch). The analysis of bioplastic was tensile strenght, elongation, modulus young, water uptake, biodegradation, and Scanning Electron Microscopy (SEM). The most significant factor of all responses was composition of filler cellulose and composition of plasticizer gliserol. The best process condition was bioplastic with composition of filler 25% b/b starch and plasticizer 0,5 gram with the value of tensile strength 17,11 MPa, elongation 4,345%, modulus young 393,786 MPa, water uptake 20,37% and biodegradation 27,78%. Scanning Electron Microscopy (SEM) analysis shows that filler distribution was not equal on corn starch matrices and still has a clod.Keywords : bioplastic, biodegradable, cellulose, filler, plasticizer